Investigating the Influence of Structure and Heterogeneity in Waste Rock Piles on Mass Loading Rates—A Reactive Transport Modeling Study - Raymond, Katherine E.; Seigneur, Nicolas; Su, Danyang; Mayer, K. Ulrich (Frontiers in Water, 2021)
Placement methods and material availability during waste rock pile (WRP) construction may create significant heterogeneities in physical and geochemical parameters (such as grain size, permeability, mineralogy and reactivity) and influence the internal pile structure. Due to the enormous scale of WRPs, it is difficult to capture the influence of heterogeneities on mine drainage composition and evolution. Although laboratory- or field-scale experimental studies have provided much insight, it is often challenging to translate these results to full scale WRPs. This study uses a numerical modeling approach to investigate the influence of physical and chemical heterogeneities, structure, and scale on the release of acid rock drainage (ARD) through 2D reactive transport simulations. Specifically, the sensitivity of drainage quality to parameters including grain size distribution, sulfide mineral weathering rates, abundance and distribution of primary minerals, and pile structure as a function of construction methods are investigated. The geochemical model includes sulfide oxidation, pH buffering by calcite dissolution, and ferrihydrite and gypsum as secondary phases. Simulation results indicate that the implications of heterogeneity and construction method are scale-dependent; when grain size distribution trends observed in a pile’s core are applied to the entirety of a pile, results between push- and end-dumping methods vary substantially—however, predicted drainage for different construction methods become more similar when features such as traffic surfaces, structural variation, and multiple benches are also considered. For all scales and construction methods investigated, simulated results demonstrate that pile heterogeneity and structure decrease peak mass loading rates 2 to 3-fold, but cause prolonged ARD release compared to the homogeneous case. These findings have implications for the economics of planning water treatment facilities for life of mine and closure operations.